Green Tax Incentives Boost Industrial Sector Participation in SDGs 7 (Access to Affordable and Clean Energy) by 2030 - Miqdamuntaqo Ferdiansa; I. B. Ketut Bayangkara (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the effectiveness of environmentally friendly tax incentives in enhancing industrial participation toward achieving Sustainable Development Goal 7, which emphasizes access to affordable and clean energy by 2030. Using a non-empirical qualitative approach based on systematic literature review and policy analysis, the study synthesizes findings from academic publications, institutional reports, and regulatory documents published between 2022 and 2026. The analysis reveals that green tax incentives, including tax holidays, tax credits, and super deductions, play a significant role in reducing investment barriers and encouraging industrial engagement in renewable energy development. However, structural challenges such as fossil fuel dependency, regulatory inconsistencies, limited institutional capacity, and uneven industrial readiness constrain their effectiveness. The study further identifies that policy integration, technological innovation, and sustainable financing mechanisms are critical in strengthening the impact of fiscal instruments. By developing a comprehensive analytical framework, this research contributes to the literature on sustainability accounting and fiscal policy, offering strategic insights for optimizing green tax incentives in supporting energy transition pathways.